APPLICATION OF DIRECT INTRUCTIONS MODEL USING GEOGEBRA APPLICATION TO IMPROVE LEARNING ACHIEVEMENT - Wahyudi Wahyudi; Turdjai Turdjai (DIADIK, 2018)
This research purpose to: describe the application of direct intructions models using the Geogebra application to improve learning achievement. This study uses classroom action research methods which are divided into three cycles. The class that was made for this study were VIII.e students totaling 21 students. Data collection techniques used in this study were obtained by observation for learning activities, while for learning achievement data using pre-test and post-test questions. The data obtained is then processed by calculating the average value for learning, and for learning achievement the data obtained is processed by looking for the average value and t-test formula. This study concludes that the application of direct intructions models uses the Geogebra application to improve accuracy and learning achievement.